Macrophage SR-BI modulates autophagy via VPS34 complex and PPARα transcription of Tfeb in atherosclerosis - Huan Tao; Patricia G. Yancey; John L. Blakemore; Youmin Zhang; Lei Ding; W. Gray Jerome; Jonathan D. Brown; Kasey C. Vickers; MacRae F. Linton (The Journal of Clinical Investigation, 2021)
Autophagy modulates lipid turnover, cell survival, inflammation, and atherogenesis. Scavenger receptor class B type I (SR-BI) plays a crucial role in lysosome function. Here, we demonstrate that SR-BI regulates autophagy in atherosclerosis. SR-BI deletion attenuated lipid-induced expression of autophagy mediators in macrophages and atherosclerotic aortas. Consequently, SR-BI deletion resulted in 1.8- and 2.5-fold increases in foam cell formation and apoptosis, respectively, and increased oxidized LDL–induced inflammatory cytokine expression. Pharmacological activation of autophagy failed to reduce lipid content or apoptosis in Sr-b1–/– macrophages. SR-BI deletion reduced both basal and inducible levels of transcription factor EB (TFEB), a master regulator of autophagy, causing decreased expression of autophagy genes encoding VPS34 and Beclin-1. Notably, SR-BI regulated Tfeb expression by enhancing PPARα activation. Moreover, intracellular macrophage SR-BI localized to autophagosomes, where it formed cholesterol domains resulting in enhanced association of Barkor and recruitment of the VPS34–Beclin-1 complex. Thus, SR-BI deficiency led to lower VPS34 activity in macrophages and in atherosclerotic aortic tissues. Overexpression of Tfeb or Vps34 rescued the defective autophagy in Sr-b1–/– macrophages. Taken together, our results show that macrophage SR-BI regulates autophagy via Tfeb expression and recruitment of the VPS34–Beclin-1 complex, thus identifying previously unrecognized roles for SR-BI and potentially novel targets for the treatment of atherosclerosis.